2019
DOI: 10.1016/j.jclepro.2019.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of supply-side and demand-side policies on energy consumption and CO2 emissions from urban passenger transportation: The case of Istanbul

Abstract: The transportation sector accounts for about a quarter of global energy consumption and energy-related carbon emissions. To design and realize sustainable urban transportation, it is vital to understand and analyze interactions between a set of dynamic factors that shape transportation patterns, behaviors, and impacts. To this end, this study aims to develop a systems dynamics (SD) model for Istanbul, Turkey to simulate its urban motorized passenger transport system for analyzing numerous policies under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…Unfortunately, as a modern necessity, energy is also the key contributor to global climate change as well as local air pollution [33]. To respond to energy security and environmental pollution pressures, energy policies have focused on supply-side issues such as economic structural change, technological improvement, and regulatory management [34]. Subsequently, demand-side policies have been gaining more attention from researchers and policymakers.…”
Section: The Role Of Energy In Economic Growthmentioning
confidence: 99%
“…Unfortunately, as a modern necessity, energy is also the key contributor to global climate change as well as local air pollution [33]. To respond to energy security and environmental pollution pressures, energy policies have focused on supply-side issues such as economic structural change, technological improvement, and regulatory management [34]. Subsequently, demand-side policies have been gaining more attention from researchers and policymakers.…”
Section: The Role Of Energy In Economic Growthmentioning
confidence: 99%
“…They also suggested that different technological progress levels have a direct and technical effect on carbon emissions. Also (Batur et al, 2019) assessed the impact of supply and demand-side policies on energy consumption and carbon emissions in Istanbul. Based on the historical data from 2000 to 2015, resulting in different scenarios they found that a 10% improvement in the fuel economy of the vehicles would lead to a 10% reduction in carbon emissions.…”
Section: Energy Consumption-pollution Nexusmentioning
confidence: 99%
“…(2), and Eq. (3), respectively [3]. The stock and flow diagram of the energy consumption and CO2 emissions of a personal car, as for example, and the total CO2 emissions were shown in Fig.…”
Section: Energy Consumption and Co2 Emissions Subsystemmentioning
confidence: 99%
“…The transportation sector accounts for about a quarter of global energy consumption and energyrelated CO2 emissions [3]. According to the IEA's report in 2019, almost 27% of the world's total final consumption of energy is from the transportation sector [4].…”
Section: Introductionmentioning
confidence: 99%